Megestrol acetate improves cardiac function in a model of cancer cachexia‐induced cardiomyopathy by autophagic modulation. Issue 5 (7th April 2016) - Musolino, Vincenzo; Palus, Sandra; Tschirner, Anika; Drescher, Cathleen; Gliozzi, Micaela; Carresi, Cristina; Vitale, Cristiana; Muscoli, Carolina; Doehner, Wolfram; von Haehling, Stephan; Anker, Stefan D.; Mollace, Vincenzo; et al.
Abstract: Background: Cachexia is a complex metabolic syndrome associated with cancer. One of the features of cachexia is the loss of muscle mass, characterized by an imbalance between protein synthesis and protein degradation. Muscle atrophy is caused by the hyperactivation of some of the main cellular catabolic pathways, including autophagy. Cachexia also affects the cardiac muscle. As a consequence of the atrophy of the heart, cardiac function is impaired and mortality is increased. Anti‐cachectic therapy in patients with cancer cachexia is so far limited to nutritional support and anabolic steroids. The use of the appetite stimulant megestrol acetate (MA) has been discussed as a treatment for cachexia. Methods: In this study the effects of MA were tested in cachectic tumour‐bearing rats (Yoshida AH‐130 ascites hepatoma). Rats were treated daily with 100 mg/kg of MA or placebo starting one day after tumour inoculation, and for a period of 16 days. Body weight and body composition were assessed at baseline and at the end of the study. Cardiac function was analysed by echocardiography at baseline and at day 11. Locomotor activity and food intake were assessed before tumour inoculation and at day 11. Autophagic markers were assessed in gastrocnemius muscle and heart by western blot analysis. Results: Treatment with 100 mg/kg/day MA significantly attenuated the loss of body weight (−9 ± 12%, P  < 0.05) and the wasting of lean and fat mass (−7.0 ± 6% and −22.4 ± 3 %, P  < 0.001 and P  < 0.05, respectively). Administration of 100 mg/kg/day MA significantly protected the heart from general atrophy (633.8 ± 30 mg vs. placebo 474 ± 13 mg, P  < 0.001). Tumour‐bearing rats displayed cardiac dysfunction, as indicated by the significant impairment of the left ventricular ejection fraction, the left ventricular fractional shortening, the stroke volume, the end dyastolic volume, and the end systolic volume. In contrast, MA significantly improved left ventricular ejection fraction, left ventricular fractional shortening, and left ventricular end systolic volume. Western blotting analysis showed an upregulation of the autophagic pathway in the gastrocnemius and hearts of the placebo‐treated tumour‐bearing rats. Treatment with MA, however, was able to modulate the autophagic markers (e.g. Beclin‐1, p62, TRAF6, and LC3) in the gastrocnemius and in the hearts of tumour‐bearing rats. Most importantly, 100 mg/kg/day MA reduced mortality [hazard ratio (HR): 0.44; 95%CI: 0.20–1.00; P  = 0.0486]. Conclusions: Megestrol acetate improved survival and reduced wasting through a marked downregulation of autophagy, occurring in both skeletal and heart muscle, the latter effect leading to a significant improvement of cardiac function. Our data suggest that MA might represent a valuable strategy to counteract the development of cancer cachexia‐induced cardiomyopathy.